Viroid Pathogenicity: One Process, Many Faces - Rosemarie W. Hammond; Robert A. Owens (Viruses, 2009)
Despite the non-coding nature of their small RNA genomes, the visible symptoms of viroid infection resemble those associated with many plant virus diseases. Recent evidence indicates that viroid-derived small RNAs acting through host RNA silencing pathways play a key role in viroid pathogenicity. Host responses to viroid infection are complex, involving signaling cascades containing host-encoded protein kinases and crosstalk between hormonal and defense-signaling pathways. Studies of viroid-host interaction in the context of entire biochemical or developmental pathways are just beginning, and many working hypotheses have yet to be critically tested.